Subjective responses to emotional stimuli during labeling, reappraisal, and distraction. - Lieberman, MD; Inagaki, T; Tabibnia, G; Crockett, M (2011)
Although multiple neuroimaging studies suggest that affect labeling (i.e., putting feelings into words) can dampen affect-related responses in the amygdala, the consequences of affect labeling have not been examined in other channels of emotional responding. We conducted four studies examining the effect of affect labeling on self-reported emotional experience. In study one, self-reported distress was lower during affect labeling, compared to passive watching, of negative emotional pictures. Studies two and three added reappraisal and distraction conditions, respectively. Affect labeling showed similar effects on self-reported distress as both of these intentional emotion regulation strategies. In each of the first three studies, however, participant predictions about the effects of affect labeling suggest that unlike reappraisal and distraction, people do not believe affect labeling to be an effective emotion regulation strategy. Even after having the experience of affect labels leading to lower distress, participants still predicted that affect labeling would increase distress in the future. Thus, affect labeling is best described as an incidental emotion regulation process. Finally, study four employed positive emotional pictures and here, affect labeling was associated with diminished self-reported pleasure, relative to passive watching. This suggests that affect labeling tends to dampen affective responses in general, rather than specifically alleviating negative affect.